Optimization of Project Acceleration Using Least Cost Scheduling Method: A Case Study - Rani, Hafnidar A.; Amin, Jurisman; Bella, Sonia Oktavia (Jurnal Linears, 2025)
The rapid growth of the construction industry demands effective project management strategies to minimize delays and optimize costs. This study analyzes project acceleration using the Least Cost Scheduling (LCS) method in the construction of State Civil Apparatus (ASN) Ministry of Public Works and Housing (PUPR) flats for National Sports Week (PON) support. The research applies Microsoft Project to determine the critical path and evaluates different acceleration scenarios by increasing working hours by 1, 2, 3, and 4 hours per day. The findings indicate that with a 4-hour work extension, the project duration can be reduced from 390 days to 325 days, achieving a time saving of 65-days. However, this acceleration increases total project costs from IDR 20,436,612,368.92 to IDR 30,830,058,031.32, representing a 50.86% cost increase. The most cost-efficient balance was achieved by extending the workday by three hours, reducing project duration to 351 days with a 45.20% cost increase. These results provide valuable insights for construction project managers in selecting efficient acceleration strategies while considering financial feasibility.